REPORT OF THE ARCTIC ICE OBSERVING AND FORECASTING PROGRAM, 1964. - NAVAL OCEANOGRAPHIC OFFICE WASHINGTON D C (1965)
The ice program conducted by the Oceanographic Office during 1964 is covered by this report. Methods of data collection and dissemination, a report of ice forecasting and reconnaissance, and concomitant ice projects are discussed. A graphic summary of ice data and oceanographic stations collected in the North American Arctic from the Bering Sea to the Denmark Strait is given for January through December. Aerial ice reconnaissance data collected in Canadian and Greenland waters by Canada and Denmark, respectively, and surface and shore observations made by Canadian and United States ships are included. (Author) See also AD-620 875.